Using pumice as an alternative to reduce biological oxygen demand and chemical oxygen demand in tough waste - Sholehah, Hijriati; Abdullah, Taufik; Azwarudin; Aprianti, Sri (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
The tofu industry is a type of industry that operates in the field of food processing from soybean raw materials. The tofu industry is dominated by small-scale businesses, most integrated into residential areas. The tofu industry has yet to process the liquid waste it produces. High environmental pollution can result in the death of aquatic biota due to lack of oxygen. This research aims to reduce BOD and COD levels that do not meet quality standards. Based on this, research was conducted to reduce the organic content in tofu liquid waste using pumice stone as a filtration medium. The research used a 2.5-inch PVC pipe with a height of 70 cm and a media size of 8 mesh, which was heated at temperatures of 50°C and 100°C. The research results after treatment showed that the initial concentration of BOD levels was 160 mg/L. After going through the filtration process with media heating treatment at 50°C and 100°C, the BOD levels were reduced to 116.8, 76.8, and 40 mg/L, respectively, with 52% and 75% reduction effectiveness. While the initial concentration of COD levels was 326 mg/L, after going through the filtration process with media heating treatment at 50°C and 100°C, the COD levels were reduced to 252 and 198 mg/L, respectively, and the effectiveness of the reduction was 23% and 39%.